PELAKSANAAN BIMBINGAN KONSELING ANAK BERKEBUTUHAN KHUSUS DI SMK N 4 PADANG - Dina Dwinita (Jurnal Penelitian Pendidikan Khusus, 2012)
The research is motivated by problems that happen in inclusive schools SMK Padang 4. Teachers at the school are not the Special Assistance and the Special Assistance is Guru Guru Counseling. Children with Special Needs Parents complained about the lack of communication between teachers with parents Counseling Children with Special Needs in providing Counseling services. Meanwhile, according to Guru Counseling cooperation between parents Children with Special Needs has been pretty well established. The research was conducted in order to determine the implementation of guidance and counseling for children with special needs in SMK N 4 Padang This study used descriptive qualitative approach, which focused on the implementation, problems, and work done by the counseling teacher in dealing with children with special needs. Subjects were all over the school. The process of data collection is done through observation, interviews, and documentation The results of this research is the implementation of the counseling that was not done properly. Constraints faced by teachers in dealing Counseling Children with Special Needs, as well as the efforts made ​​by the counseling teacher in dealing with children with special needs. And besides job as a teacher by the Special Advisor Counseling teacher, in the absence of tenag counselor in school. So many tasks that should be implemented to be hampered by too much coverage should be done in about the same time. For the future X is expected to increase the sense of responsibility in carrying out tasks that could Children with Special Needs maximum assistance in education. Other than that required additional teachers, so that improvements can be made ​​to progress.